1975
DOI: 10.1073/pnas.72.10.3858
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent absorption and selective scattering changes at 518 nm in chloroplast thylakoid membranes.

Abstract: The light-induced absorbance change at 518 nm of isolated chloroplasts consists of a rapid phase, and a slow phase which is complete in about 20 sec. The slow component of the 518 nm absorbance change correlates with the light-induced change in 900 light scattering at 518 nm. Both show a similar time course, similar pH dependence with a maximum at pH 6.0, and similar sensitivity to inhibitors and to treatment of the chloroplasts with a low concentration of glutaraldehyde. Their light minus dark difference spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The phenomenon was found in leaves of many common plant species. Thorne et al (1975) confirmed the observations of Heber and, using isolated thylakoid membranes, reported that the conformational changes are triggered by proton uptake leading to alterations in the membranes. Thorne etal.…”
Section: ( 3 ) Photosynthesissupporting
confidence: 89%
“…The phenomenon was found in leaves of many common plant species. Thorne et al (1975) confirmed the observations of Heber and, using isolated thylakoid membranes, reported that the conformational changes are triggered by proton uptake leading to alterations in the membranes. Thorne etal.…”
Section: ( 3 ) Photosynthesissupporting
confidence: 89%
“…The rapid change, frequently seen as a spike in kinetic measurements, indicates the formation of a membrane potential in or across the thylakoid membrane. The subsequent slow change is associated with lightdependent energization of the thylakoid membrane and establishment of a proton gradient across the membrane (26,41). Both wild-type and viridis-n 34 leaves showed the fast component of the 518 nm change.…”
Section: Resultsmentioning
confidence: 99%
“…The slowly reversible component was totally abolished in the presence of Dq'T and follows the same kinetics as AA510. Like AAs10 this component of AA540 is undoubtedly caused by changes in the zeaxanthin level whereas the rapidly reversible component most probably is associated with changes in selective light-scattering (Heber 1969, Thorne et al 1975. The light-scattering change has been thought to be caused by conformational changes of the thylakoid membrane and has been used as an indicator of membrane energization (Heber 1969, Kobayashi et al 1982.…”
Section: Light-induced Absorbance Changes and Zeaxanthin Formationmentioning
confidence: 99%